2015
DOI: 10.1002/asi.23582
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of journal rankings by network flows with different amounts of memory

Abstract: As the number of scientific journals has multiplied, journal rankings have become increasingly important for scientific decisions. From submissions and subscriptions to grants and hirings, researchers, policy makers, and funding agencies make important decisions with influence from journal rankings such as the ISI journal impact factor. Typically, the rankings are derived from the citation network between a selection of journals and unavoidably depend on this selection. However, little is known about how robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…When going from rankings based on counting links to measuring the average visit frequency of a random walker on a standard network,that is, calculating the PageRank 6 , the importance of neighbours becomes evident. Similarly, when going to PageRank on a network with secondorder memory, the amount of flow received from neighbours also depends on the flow's origin 15,48 . We define a generalized secondorder PageRank as the stationary solution of equation (6) …”
Section: First-order Markovmentioning
confidence: 99%
“…When going from rankings based on counting links to measuring the average visit frequency of a random walker on a standard network,that is, calculating the PageRank 6 , the importance of neighbours becomes evident. Similarly, when going to PageRank on a network with secondorder memory, the amount of flow received from neighbours also depends on the flow's origin 15,48 . We define a generalized secondorder PageRank as the stationary solution of equation (6) …”
Section: First-order Markovmentioning
confidence: 99%
“…Zhang proposed the HR-PageRank algorithm to evaluate journal impact via weighted PageRank according to the author's H-index, and relevance between citing and cited papers [108]. Bohlin et al [109] studied the different performances of zero-(the classical Markov model), firstand second-order Markov model while ranking journals and found that higher-order Markov models performed better and were more robust. Some evaluation methods consider the structural position of journals in the journal citation network.…”
Section: Network-based Evaluation Methods and Indicesmentioning
confidence: 99%
“…In that case, their connections would be too tenuous to regard them as providing meaningful scholarly cross-fertilization. We wanted to ensure that the paths needed to reach the Lowry et al sample were no longer than two steps in each direction (for the rationale: Bohlin, Viamontes Esquivel, Lancichinetti, & Rosvall, 2016). That is, each journal should be able to reach every Lowry et al journal with no more than one indirect cross-citation.…”
Section: A2 Journal Paths and The Formation Of The Broader Samplementioning
confidence: 99%